2020
DOI: 10.1002/batt.201900205
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Photoactive Zn‐Air Batteries Using NiCo2S4 as an Efficient Bifunctional Photocatalyst towards OER/ORR at the Cathode

Abstract: Using free solar energy in oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) electrocatalysts to enhance the efficiency of zinc‐air batteries (ZABs) has not yet been widely investigated. Herein, we report a photoactive bifunctional catalyst of spinel‐type NiCo2S4 (NCS) urchin‐like structure with rich mesopores and direct band gap energies of ca. 1.4 and 2.4 eV. The NCS catalyst exhibits high catalytic activities for both OER (ɳ=338 mV at 10 mA cm−2) and ORR (ɳ=475 mV at E1/2), comparable to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…The band gaps of ZCS, 10CS/ZCS, and CS were 2.25, 2.1, and 1.3 eV, respectively, as shown in Figure c. The reduced band gap of the composite sample facilitated the production of photogenerated electrons under visible light excitation, which was conducive to the occurrence of the photocatalytic hydrogen production reaction …”
Section: Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The band gaps of ZCS, 10CS/ZCS, and CS were 2.25, 2.1, and 1.3 eV, respectively, as shown in Figure c. The reduced band gap of the composite sample facilitated the production of photogenerated electrons under visible light excitation, which was conducive to the occurrence of the photocatalytic hydrogen production reaction …”
Section: Results and Discussionmentioning
confidence: 95%
“…The reduced band gap of the composite sample facilitated the production of photogenerated electrons under visible light excitation, which was conducive to the occurrence of the photocatalytic hydrogen production reaction. 36 The separation of photogenerated electrons and holes is the most important step in determining the photocatalytic reaction. The transient photocurrent and impedance usually reflect the photogenerated electron concentration and the electron transfer process, and the fluorescence spectrum reflects the compound of photogenerated electrons and holes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, metal sulfides and metal phosphides can also be used as photoelectrodes for photoassisted rechargeable ZABs, including NiCo 2 S 4 , and Ni 12 P 5 @NCNT. 117,118 For example, photoassisted ZABs with NiCo 2 S 4 photoelectrodes exhibit stable cycling performance with charge and discharge potential plateaus of ∼1.92 V and ∼1.32 V at a current density of 2 mA cm −2 under light illumination, increasing the energy efficiency from 59.2% to 68.8%. 117 Furthermore, when Ni 12 P 5 @NCNT was introduced into the ZAB, the charge/discharge voltage and energy efficiency under light were also improved due to the good photocatalytic activity of the dual functional Ni 12 P 5 @NCNT air cathode (Fig.…”
Section: Integrated Two-electrode Configuration Of Pes Batteriesmentioning
confidence: 99%
“…It is demonstrated that choosing semiconductor with more negative CB positions, appropriate VB positions, and high photoelectrochemical stability is effective to address the high over potential issue of zinc–air battery. Besides, metal sulfides, metal oxides, metal phosphides, and their composites can be also used as photoelectode in photo‐assisted rechargeable zinc–air battery, including NiCo 2 S 4 , [ 90 ] Co 3 O 4 , [ 91 ] CdS/TiO 2 , [ 92 ] ZnS/CdSe/CdS/TiO 2 , [ 93 ] TiO 2 /carbon papers, [ 94 ] and Ni 12 P 5 @NCNT. [ 95 ] For example, the photo‐assisted zinc–air battery with NiCo 2 S 4 photoelectode presents a stable cycling performance with the charge and discharge potential plateaus of ~1.92 V and ~1.32 V at a current density of 2 mA cm −2 under light illumination, increasing the energy efficiency from 59.2% to 68.8%.…”
Section: Photo‐assisted Rechargeable Metal Zinc Batteriesmentioning
confidence: 99%